APPLICATION THE DRIS EQUATION TO ASSESS THE NUTRIENT STATUS OF DUKAN AND DUHOK LAKES IN NORTHERN OF IRAQ - Darwesh, Dalshad A.; Shekha, Yahya A.; Toma, Janan J. (Diyala Agricultural Sciences Journal, 2017)
This investigation was conducted to study the nutrient status of different lakes and to determine the productivity status of lakes by comparing the results of DRIS approach with the lakes productivity equations. Data for application of DRIS and TSI equations were collected from previous studies for Dukan and Duhok Lakes that conducted at different studies periods while water samples were taken and analyzed during 2013. The results of nutrient index showed that the Dokan Lake was more balance or adequate status of nutrient in 1980 compared with 2014, because there imbalance of nutrients indices recorded lower value (193.60) in 1980 compared with 2014 which attained (413.34). However data analysis was revealed that the lower value of NBI (129.52) was recorded in 2013 in comparison to the higher value NBI in 2000 in Duhok Lake. The DRIS also computed an overall index, which is the sum of the absolute sum of all DRIS indices, the lesser NBI the imbalance among nutrient referred to more productivity. In general the result indicate that nutrient index and nutrients imbalance index showed more balance in Dukan Lake in previous period in comparison with the recent period, vice versa for Duhok Lake. From TSI value revealed that the productivity of Dukan Lake decreased from (56.41) to (53.07) during 1980 and 2014, while the productivity of the Duhok Lake increased from (30.11) to (32.63) during 2000 to 2013.